An Analysis of the Role of Middle Leaders in Parental Involvement and Learner Discipline in Gauteng Province Middle Schools - Mpipo Zipporah Sedio; Vimbi Petrus Mahlangu (Iranian Journal of Educational Research)
Objective: This study examines the function of middle leaders in fostering parental engagement and overseeing student discipline in middle schools located in Gauteng Province. Middle leaders, often department heads or senior educators, are essential in connecting school leadership with classroom implementation. Methods: The study examines the methods by which these leaders include parents in fostering their children's educational and behavioral growth, as well as their execution and supervision of disciplinary rules. Results: It also analyses the difficulties they encounter in reconciling these obligations and their impact on fostering a positive school culture. The study seeks to elucidate successful leadership techniques that promote collaboration between educational institutions and parents, while preserving a disciplined learning atmosphere. Conclusions: Comprehending the function of middle leaders is crucial for enhancing learner behavior and parental involvement, hence boosting educational achievements in Gauteng middle schools.